2018
DOI: 10.1002/clc.22882
|View full text |Cite
|
Sign up to set email alerts
|

Stem‐cell therapy in ST‐segment elevation myocardial infarction with reduced ejection fraction: A multicenter, double‐blind randomized trial

Abstract: BackgroundLeft ventricular ejection fraction (LVEF) is a major determinant of long‐term prognosis after ST‐segment elevation myocardial infarction (STEMI). STEMI patients with reduced LVEF have a poor prognosis, despite successful reperfusion and the use of renin‐angiotensin‐aldosterone inhibitors.HypothesisIntracoronary infusion of bone marrow–derived mononuclear cells (BMMC) may improve LVEF in STEMI patients successfully reperfused.MethodsThe main inclusion criteria for this double‐blind, randomized, multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…But, positive remolding leads to Lumen eccentricity and plaque stress increase, and the plaque can easily fracture 19. The changes in some metabolism factors such as postprandial metabolism can also increase blood coagulation, thus leading to the increase of cardiovascular event risk, and unstable clinical manifestations of CHD patients 20,21. Linear correlation analysis showed that coronary artery lesion was positively correlated with LVEF and calcified plaque (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…But, positive remolding leads to Lumen eccentricity and plaque stress increase, and the plaque can easily fracture 19. The changes in some metabolism factors such as postprandial metabolism can also increase blood coagulation, thus leading to the increase of cardiovascular event risk, and unstable clinical manifestations of CHD patients 20,21. Linear correlation analysis showed that coronary artery lesion was positively correlated with LVEF and calcified plaque (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The ineffectiveness of stem cell transplantation in AMI patients was recently confirmed in CAREMI [ 37 ], MiHeart/AMI [ 38 ], BAMI [ 39 ] and Cardiovascular Cell Therapy Research Network (CCTRN) trials [ 40 ] including a total of 665 patients showing no improvement in LV remodelling and LVEF as well as in reducing the time to all-cause mortality.…”
Section: Cons: Trials Showing No Benefit Of Stem Cells Therapy In Amimentioning
confidence: 99%
“…In the following decade, at least ten randomized and multicenter trials using mostly ABMMC, but also selected bone marrow cells, in IHD occurred in the world. All of these trials did not find additional benefits to standard therapy (Traverse et al, 2011;Perin et al, 2012;Traverse et al, 2012;Sürder et al, 2013;Choudry et al, 2016;Sürder et al, 2016;Quyyumi et al, 2017;Wollert et al, 2017;Fernández-Avilés et al, 2018;Nicolau et al, 2018), mostly in acute but one in chronic FIGURE 1 | Cell-based therapies for heart failure. Cell types used in clinical trials include bone marrow mononuclear cells (BMMC), CD34 + mobilized with G-CSF, bone marrow and adipose tissue-derived mesenchymal stromal cells (MSC), embryonic stem cells (ESC), and induced pluripotent stem cells (iPSC).…”
Section: Cell-based Therapies For Ischemic Heart Diseasementioning
confidence: 99%